2017
DOI: 10.3390/toxins9120383
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adding Clostridium sp. WJ06 on Intestinal Morphology and Microbial Diversity of Growing Pigs Fed with Natural Deoxynivalenol Contaminated Wheat

Abstract: Deoxynivalenol (DON) is commonly detected in cereals, and is a threat to human and animal health. The effects of microbiological detoxification are now being widely studied. A total of 24 pigs (over four months) were randomly divided into three treatments. Treatment A was fed with a basal diet as the control group. Treatment B was fed with naturally DON-contaminated wheat as a negative control group. Treatment C was fed with a contaminated diet that also had Clostridium sp. WJ06, which was used as a detoxicant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 48 publications
6
40
0
Order By: Relevance
“…Xiao et al found that DON significantly reduced ADG and ADFI in weaned piglets through a 30-day feeding trial [8]. Li et al also showed that piglets fed a DON-contaminated diet showed significantly decreased growth performance [32]. Goyarts et al found that DON did not change the feed-to-gain ratio of grower pigs, while Bergsjo et al showed that grower piglets fed DON-contaminated diets had reduced feed utilization efficiency [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Xiao et al found that DON significantly reduced ADG and ADFI in weaned piglets through a 30-day feeding trial [8]. Li et al also showed that piglets fed a DON-contaminated diet showed significantly decreased growth performance [32]. Goyarts et al found that DON did not change the feed-to-gain ratio of grower pigs, while Bergsjo et al showed that grower piglets fed DON-contaminated diets had reduced feed utilization efficiency [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Until now, few studies have been conducted to investigate the effects of the DON and ZEN mycotoxins on the pig gastrointestinal microbiota; in particular, the effects of ZEN on the gastrointestinal microbiota are largely unknown. Previous studies have examined the effects of naturally mycotoxin-contaminated feeds on the gut microbiota, but no reports are available on the microbial composition of the colonic contents of pigs fed commercially purified DON and ZEN [ 20 , 24 ]. Therefore, we analyzed the colon contents of pigs fed commercially purified DON and ZEN, to compare microbial abundances in the control, DON, and ZEN dietary groups, for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies of the effects of the DON and ZEN mycotoxins on the pig gastrointestinal microbiota are lacking; in particular, the effect of ZEN on the pig gut microbiota remains unclear. Recently, Li et al [ 20 ] have studied the intestinal microbial diversity in pigs fed a basal diet, naturally DON-contaminated wheat, and a feed contaminated with Clostridium sp. WJ06.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for DG-6 and DII-9, 3 other bacteria, BBSH797 from bovine rumen [32], LS100 from chicken intestine [31], and Clostridium sp. WJ06 (WJ06) from animal intestine [39] have been identified as capable of DON de-epoxidation. BBSH797 belongs to the family Coriobacteriaceae.…”
Section: Discussionmentioning
confidence: 99%